1982
DOI: 10.1111/j.1365-2494.1982.tb01598.x
|View full text |Cite
|
Sign up to set email alerts
|

The diet ingested by sheep grazing swards differing in white clover and perennial ryegrass content

Abstract: A series of twenty-four swards containing different proportions of white clover (OOO-O55) and perennial ryegrass were created by using different seed mixtures, herbicide applications and previous cutting frequencies. These swards were used to study the diet of oesophagcally-fistulated wether sheep which grazed the various swards for a 30-min period after 1. 2 and 3 weeks of regrowth.The proporiion of white clover In the diet was generally greater than that in the sward. Fiftyseven percent ofthe variation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
76
2
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 6 publications
13
76
2
1
Order By: Relevance
“…I), which may reflect the increased weed content of the diet as sward clover content increases. Milne et al (1982) reported clover selection in a vertical plane from within the grazed stratum of swards after I, 2, and 3 weeks regrowth. Intercept, and hence degree of selection, increased with the longer regrowth periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I), which may reflect the increased weed content of the diet as sward clover content increases. Milne et al (1982) reported clover selection in a vertical plane from within the grazed stratum of swards after I, 2, and 3 weeks regrowth. Intercept, and hence degree of selection, increased with the longer regrowth periods.…”
Section: Discussionmentioning
confidence: 99%
“…This superiority, together with the ability to fix nitrogen, has led to recommendations to increase the white clover content of New Zealand pasture and hence the nutrition of all classes of livestock (Ulyatt et al 1976). Milne et al (1982) deliberately created -swards that differed in their vertical distribution of white clover, but there.is little information on the effect of manipulation of the horizontal distribution of white clover on diet selection, or of the influence of other sward components. This study investigates the effect of the horizontal distribution of white clover on diet selection.…”
Section: Introductionmentioning
confidence: 99%
“…Grazing ruminants vary bite mass, bite rate and grazing time in response to changes in sward conditions (Hodgson 1981;Milne et al 1982;Penning et al 1991;Gibb et al 1997). Bite mass, for example, increases with increased sward height and bulk density, ranging from 0.25 to 4 g DM in cattle offered micro-swards of lucerne (Medicago sativa) and paspalum (Paspalum dilatatum) (Ungar 1996) and the rate of biting is related to the ease of prehensions, herbage shear force and bite mass, as smaller mouthfuls often lead to an increase in bite rate.…”
Section: Factors Limiting Intake Of Grazing Cowsmentioning
confidence: 99%
“…Diet and sward composition (above 4 cm) were similar (Table 4). In temperate swards, there is evidence suggesting that the diet of oesophageally fistulated animals may reflect the composition of the top strata of the sward, indicating substantially unselective grazing (Milne et al 1982;Illius et al 1992;Clark 1993;Montossi et al 1994). Though oesophageally fistulated animals were older than the experimental lambs, this is unlikely to have materially affected diet selection (Hodgson & Rodriguez 1971).…”
Section: Diet Selectionmentioning
confidence: 99%